Polemik Waw Thamāniyah: Analisis Berdasarkan Nas Dan Bahasa Arab - Muhammad Hakim Kamal; Ahmad Bazli Ahmad Hilmi; Khairul Asyraf Mohd Nathir; Mohd Farhan Md Ariffin; Khairulnazrin Nasir (Tamu, 2025)
Index